Socioeconomic Factors That Contribute to Criminal Behaviors in Louisiana: Policy Implications - Akinbobola, Babatunde Ademola (2021)
This study investigates the socioeconomic factors that contribute to criminal behaviors in Louisiana by focusing on the residents’ perceptions. The study used a survey instrument through the help of google doc (internet) to sample 110 residents of Louisiana across the following cities: Lafayette, Baton Rouge, New Orleans, and Lake Charles. The study was purely descriptive in nature. The study found that the following socioeconomic factors influences criminal activities in the state of Louisiana: modern society, high poverty, low education, and race/ethnicity. The majority of the respondents were of the opinion that the modern society and its structure as well as low education attainment, and high poverty rates play significant role in influencing criminal behaviors. The study therefore suggests that policymakers and law enforcement agencies should enforce the free education policy in the state in order increase the number of people attaining high school certificates/education and to some extent college education. The study further suggests that policymakers should also make available financial aid resources that could easily be accessible by students as a way to motivate them to go to school. More jobs and equal opportunities should be given to all citizens irrespective of body color (or race) to minimize income inequality gap, and poverty among the citizens. Keywords: Crime, Education, Modern-Society, Poverty, Criminal-behavior, Socioeconomic, and Policy DOI: 10.7176/PPAR/11-7-04 Publication date:August 31st 202